Development of Data Warehouses for Production Controlling Systems - Eicker, Stefan; Jung, Reinhard; Nietsch, Michael; Winter, Robert (Innovation in Technology Management - The Key to Global Leadership, Proceedings PICMET '97, 1997)
Standardized software packages cannot be utilized for production controlling data warehouse systems because the relevant information objects are too complex, and because many heterogeneous data sources have to be integrated. For transactional systems, methodologies and tools for the development of individual software have been developed. Therefore, key components of a CASE-based methodology for data warehouse development are proposed that extend existing conceptual modeling and schema integration methods and complement them by novel concepts for the generation of appropriate data loading, data scrubbing and information derivation procedures. The methodology was applied to develop a production controlling data warehouse for a large mechanical engineering company, and experience from this application is summarized.